1974
DOI: 10.1017/s0016756800000406
|View full text |Cite
|
Sign up to set email alerts
|

A possible large-scale sinistral displacement along the Great Glen Fault in Scotland

Abstract: SummaryComparison of Old Red Sandstone palaeomagnetism for NW Scotland and Norway lead to the hypothesis of a 200–300 km sinistral movement along the Great Glen Fault. The displacement is thought to be of late Caledonian (late Devonian) age. The new palaeogeographic reconstruction of Northern Britain (prior to late Caledonian times) seems to have interesting geological implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Substantial post-Devonian strike-slip faulting along the GGF and its conceivable extension to Shetland, WBF, has been postulated from palaeomagnetic data (Storetvedt 1974(Storetvedt , 1987Van der Voo & Scotese 1981). On the assumption that the A component represented the genuine Devonian palaeo-field, Van der Voo & Scotese (1981) suggested a sinistral displacement in the order of 2000 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial post-Devonian strike-slip faulting along the GGF and its conceivable extension to Shetland, WBF, has been postulated from palaeomagnetic data (Storetvedt 1974(Storetvedt , 1987Van der Voo & Scotese 1981). On the assumption that the A component represented the genuine Devonian palaeo-field, Van der Voo & Scotese (1981) suggested a sinistral displacement in the order of 2000 km.…”
Section: Discussionmentioning
confidence: 99%
“…It is substantiated, however, that A is secondary and originates from pervasive late Palaeozoic-early Mesozoic magnetic overprinting. The model proposed by Storetvedt (1974, 1988) relies on the assumption that the B component is the true Middle-Upper Devonian palaeofield. In Storetvedt's (1987) latest model, the GGF underwent at least 600km sinistral displacement in late Devonian times followed by a later dextral phase in Permian times.…”
Section: Discussionmentioning
confidence: 99%
“…The combined data of the two studies must be regarded as reasonable evidence for the following two conclusions: (a) there appears to be a direct link-up between the Great Glen Fault and the Walls Boundary Fault and (b) a large-scale sinistral movement seems to have taken place along this fracture zone. It should be made quite clear, however, that my juxtaposition of southern Shetland with Caithness (Storetvedt, 1974) merely corresponds to the minimum displacement which is necessary for removing the palaeomagnetic discordance across the fault. Based on data then available it was impossible to set a reasonable upper limit of the displacement.…”
mentioning
confidence: 97%
“…SIR, -In a recent paper Storetvedt (1974) has suggested that there may have been a late Caledonian (i.e. late Devonian) sinistral movement of 200-300 km along the Great Glen Fault.…”
mentioning
confidence: 99%
See 1 more Smart Citation